Matrix metalloproteinase-2 of human carotid atherosclerotic plaques promotes platelet activation - Lenti, Massimo; Falcinelli, Emanuela; Pompili, Marcella; Rango, Paola De; Conti, Valentina; Guglielmini, Giuseppe; Momi, Stefania; Corazzi, Teresa; Giordano, Giuseppe; Gresele, Paolo (Thrombosis and Haemostasis, 2014)
Purified active matrix metalloproteinase-2 (MMP-2) is able to promote platelet aggregation. We aimed to assess the role of MMP-2 expressed in atherosclerotic plaques in the platelet-activating potential of human carotid plaques and its correlation with ischaemic events. Carotid plaques from 81 patients undergoing endarterectomy were tested for pro-MMP-2 and TIMP-2 content by zymography and ELISA. Plaque extracts were incubated with gel-filtered platelets from healthy volunteers for 2 minutes before the addition of a subthreshold concentration of thrombin receptor activating peptide-6 (TRAP-6) and aggregation was assessed. Moreover, platelet deposition on plaque extracts immobilised on plastic coverslips under high shear-rate flow conditions was measured. Forty-three plaque extracts (53%) potentiated platelet aggregation (+233 ± 26.8%), an effect prevented by three different specific MMP-2 inhibitors (inhibitor II, TIMP-2, moAb anti-MMP-2). The pro-MMP-2/TIMP-2 ratio of plaques potentiating platelet aggregation was significantly higher than that of plaques not potentiating it (3.67 ± 1.21 vs 1.01 ± 0.43, p<0.05). Moreover, the platelet aggregation-potentiating effect, the active-MMP-2 content and the active MMP-2/pro-MMP-2 ratio of plaque extracts were significantly higher in plaques from patients who developed a subsequent major cardiovascular event. In conclusion, atherosclerotic plaques exert a prothrombotic effect by potentiating platelet activation due to their content of MMP-2; an elevated MMP-2 activity in plaques is associated with a higher rate of subsequent ischaemic cerebrovascular events.
Keywords: Atherosclerotic plaques; biomarker; matrix metalloproteinases; platelets; TIA/stroke